2017
DOI: 10.1039/c6ra26678a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ADAM17/TACE activity by zinc-chelating rye secalin-derived tripeptides and analogues

Abstract: Rye secalin-derived cysteine-containing tripeptides and analogues inhibited ADAM17 activity via active site zinc coordination, hydrogen bonds and hydrophobic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…A recent study on rye secalin‐derived tripeptides (QCA and CQV) and its analogues (QVC and QCV) showed the dose‐dependent inhibition of “A disintegrin and metalloproteinase 17” (ADAM17) or TNF‐α converting enzyme (TACE) (Udechukwu et al, ). This catalytic inhibition of ADAM17 was zinc‐chelation dependent as shown by the cysteine‐containing tripeptides which interacted with the zinc cofactor.…”
Section: Anti‐inflammatory Peptides and Structural Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on rye secalin‐derived tripeptides (QCA and CQV) and its analogues (QVC and QCV) showed the dose‐dependent inhibition of “A disintegrin and metalloproteinase 17” (ADAM17) or TNF‐α converting enzyme (TACE) (Udechukwu et al, ). This catalytic inhibition of ADAM17 was zinc‐chelation dependent as shown by the cysteine‐containing tripeptides which interacted with the zinc cofactor.…”
Section: Anti‐inflammatory Peptides and Structural Requirementsmentioning
confidence: 99%
“…Furthermore, CQV showed better quenching than its analogues QVC and QCV, despite structural similarities which suggested that the relative amino acid position played an essential role in facilitating the interaction with the enzyme as different peptides would be positioned differently on the enzyme. Molecular docking experiments showed that the peptides interacted with the active site through a series of hydrogen bonds, zinc coordination, and hydrophobic interactions and primarily occupied the S1 and S1′ sites of the enzyme (Udechukwu et al, ).…”
Section: Anti‐inflammatory Peptides and Structural Requirementsmentioning
confidence: 99%
“…Although this may seem paradoxical comparison with the results obtained by Madrigal and colleagues (2002) in the cortex, it is likely that the hippocampus undergoes a constrained increase in secreted Tnf-α at the protein level via increased TACE-induced cleavage of pro-Tnf protein already present in the cytosol, and changes at the mRNA level may occur earlier than the time-points examined in the present study ( Madrigal et al, 2002 ; Gooz, 2010 ). Cleavage of pro-Tnf may be facilitated by increased zinc availability, as it has been shown previously that TACE is a zinc-dependent metalloprotease and its catalytic activity can be inhibited by zinc chelating agents ( Moss et al, 2001 ; Udechukwu et al, 2017 ). In this study, we demonstrated that exposure to 60 minutes of restraint stress increased expression of the zinc transporter (Zip14) in the dorsal hippocampus of vehicle-treated animals, an effect that was ameliorated by PF-3845 treatment.…”
Section: Discussionmentioning
confidence: 93%
“…For example, 4-(2-pyridylazo) resorcinol and free Zn 2+ form a red-colored complex whose absorbance can be measured at 500 nm. This approach was used to determine the zinc-chelating capacity of whey protein hydrolysates [ 24 ] and rye secalin-derived tripeptides and their analogues [ 33 ]. Furthermore, the ethylenediaminetetraacetic acid (EDTA) complexing titration assay, involving the addition of xylenol orange and hexamethylenetetramine, was developed to determine zinc content.…”
Section: Methods For the Determination Of The Mineral-chelating Acmentioning
confidence: 99%